Cosimo Perrotta , Salvatore Rizzello , Claudia Sunna, 2023, Human Capital. The Driving Force for Economic Development, Palgrave Macmillan, London, 164 pp., ISBN 978-3-031-34493-0. - Trincado Aznar, Estrella (Iberian Journal of the History of Economic Thought, 2024)